Extraction and Separation of Polysaccharides from Radix isatidis and their Effects Towards Hemagglutinin Protein of Influenza Virus - Yang, Zi-Feng; Hu, Ping; Zhong, Shan; Chen, Ye; Li, Li; Li, Xu-Zhao; Li, Chuyan; Li, Jing; Wang, Yu-Tao (Asian Journal of Chemistry, 2015)
In this study, the anti-influenza virus effects of the polysaccharides of Radix isatidis and its possible target were explored. The hot water reflux extraction and stepwise ethanol precipitation were performed to extract and separate the polysaccharides from R. isatidis, the isolated constituents' activities against the influenza virus were subsequently evaluated through in vitro experiments. The ELISA assay was performed to verify the binding ability of 80 % alcohol-precipitated crude polysaccharides against the hemagglutinin (HA) of influenza A virus (A/PR/8/34, H1N1). The 70, 80 and 90 % alcohol-precipitated crude polysaccharides extracted from R. isatidis exhibited the anti-influenza virus activities,with the selection indexes (SI) as 2.69,7.52 and 5.75, respectively. Furthermore, the ELISA results showed that this constituent existed the specific binding capacity with the influenza virus HA with a dose-dependent manner. The 80 % alcohol-precipitated crude polysaccharides was one of the active components of this medicinal plant and the influenza virus HA protein might be its active target.